Meneropong maraknya pinjaman online di kalangan mahasiswa: motif dan dampak terhadap perilaku konsumtif - Hidayah, Fitriana Nurochmatul; Nugroho, Bima Setyo; Ardiati, Aulia Rizky; Tsaqyfa, Mazaya Najmy; Hakim, M. Akmal; Ridlwan, Ahmad Ajib (Jurnal Ilmu Manajemen, 2023)
This research examines and analyzes the influence of lifestyle, advertising, and ease of access on consumptive behaviour, as well as the influence of consumptive behaviour on interest in online loans and the influence of lifestyle on interest in online loans, which is moderated by consumptive behaviour. The quantitative method used in this research was with a population and research sample of 169 students with sampling using the Slovin formula. The statistical analysis used in this research is the Structural Equation Model (SEM) approach with the help of SmartPLS 3.0 software. The results of this research show that lifestyle influences consumer behaviour. Apart from that, advertising and ease of access also have a positive and significant effect on consumer behaviour. Meanwhile, consumer behaviour also has a positive and significant effect on interest in online loans. Meanwhile, consumer behaviour also moderates the relationship between lifestyle and online loans. Based on the research results, the theoretical implication of this research is that lifestyle, ease of access, and advertising can influence a person's consumptive lifestyle, which can direct someone to online loans, so students must pay attention to spending for future needs, so that the dangerous impacts caused by loans online may be reduced during the study period. Meanwhile, this research it can be used as input for students regarding their responsibilities in managing finances and creating awareness to reduce consumer lifestyles, which can lead them to online loans which have several negative impacts.